Vídeos educacionais para pacientes de transplante de córnea - Santos, Lucyara Silvares dos (2023)
Corneal transplantation is a surgical procedure in which the diseased cornea is replaced by a healthy cornea from a deceased donor, being one of the main mechanisms of visual rehabilitation of corneal diseases. In this context, the nurse must carry out the nursing process based on a theoretical framework in a systematized and dynamic way to plan care through qualified assistance in which they can use educational technologies as a form of teaching and learning. Objective: Create educational videos about care related to corneal transplantation for patients. Methodology: This is a methodological study, for the development of educational technologies, such as videos, in which three stages were followed: 1) Pre-production (selection of content, structuring of video content, validation of content by experts, preparation of scripts, preparation of storyboards.); 2) Production: preparation of scenes for the six educational videos; 3) Post-production: editing of educational videos. Results/Products: The content to compose the educational videos was created and evaluated by experts regarding information, language and target audience, with a content validity index greater than 0.8. The storyboards of the series of educational videos were created to guide care in the pre- and post-operative period of corneal transplantation, which later became the 6 videos entitled: “What is cornea”, “what is cornea transplant”, “hand washing care”, “correct use of eye drops”, “preoperative care for corneal transplantation” and “postoperative care for corneal transplantation. Each video has an average duration of 1 minute and 50 seconds, with clear, objective language suitable for the audience served by the Ophthalmology unit of the Cassiano Antonio de Moraes University Hospital. Conclusions: The technology developed is characterized as an innovative tool to guide viewers on pre- and post-operative care for corneal transplantation and makes it possible to transmit information through audiovisual resources in a playful and creative way to provide a more enjoyable learning process. simple and dynamic. This research was carried out with the financial support of notice 28/2019 of the agreement between the Federal Nursing Council - and the Coordination for the Improvement of Higher Education Personnel.